Effects of majority members' positive intergroup contact on minority members' support for ingroup rights: Mobilizing or demobilizing effects?. (25th April 2017) - Kauff, Mathias; Green, Eva G. T.; Schmid, Katharina; Hewstone, Miles; Christ, Oliver
Abstract: While some research suggests that ethnic and cultural diversity hinders societal cohesion, other studies show that it promotes intergroup contact opportunities, which, if exploited, help to overcome intergroup prejudice. Recently, however, intergroup contact theory has been criticized for neglecting the wider social context as well as for ignoring potential demobilizing contact effects for minority members. Using two cross‐sectional general population surveys (European Social Survey in 22 countries, Swiss MOSAiCH), we address these criticisms by examining whether ethnic majority members' positive contact influences ethnic minority members' support for ingroup rights at the social context level. Applying multilevel path analysis, we show that minority members are more likely to support anti‐discrimination laws and immigrant rights when living in social contexts in which majority members have positive intergroup contact experiences. Theoretical and practical implications of our findings are discussed for understanding how minority groups are affected by the climate of the social context they reside in.